GLOBAL TRENDS IN CARDIAC REHABILITATION AS SECONDARY PREVENTION FOR ACUTE CORONARY SYNDROME : ANALYSES BIBLIOMETRICS 2010-2025 - Subhan Ulan; Azizah Khoiriyati (Universitas Kadiri, 2026)
Acute Coronary Syndrome (ACS) is a life-threatening cardiovascular disease which leads to high morbidity and mortality all over the world. Cardiac rehabilitation (CR) is considered a comprehensive approach that can improve functional ability and quality of life and reduce recurrent cardiovascular events in patients with ACS. However, no bibliometric approach has been published to comprehensively analyze the scientific achievements and worldwide research trends on CR as secondary prevention in ACS. This study was based on bibliometric analysis to explore the worldwide research trends, scientific progress and research hotspots of CR as a secondary prevention therapy for ACS. Methods conducted a bibliometric study of publications indexed in the Scopus database between 2010 and 2025. Appropriate articles were searched using pre-determined search strategies specific to CR and ACS. VOSviewer software was used to evaluate and visualize publication patterns, countries, journals, citations, co-authorship networks, and keyword co-occurrence. Totaly 552 publications were reviewed. The production of publications showed a steady increase, especially from 2021 onwards. The United States was also the top contributor in the number of publications and international collaborations. The most important study questions were exercise-based cardiac rehabilitation, reduction of mortality, enhancement of quality of life and secondary prevention in patients with coronary heart disease. Conclusion: Research on CR for secondary prevention of ACS has greatly expanded over the past decade, and is expected to increasingly focus on technology-based interventions, telemedicine and more accessible rehabilitation services worldwide